PENGARUH CAR, BOPO, LDR DAN NIM TERHADAP ROA DAN PERUBAHAN LABA - Martini, Luh Kadek Budi; Suardana, Ida Bagus Raka (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
The purpose of this study is to determine the effect of Capital Adequacy Ratio, Operating Revenue Operating Expense, Loan to Deposit Ratio, and Net Interest Margin to Return On Assets and Profit Change. This research was conducted on Rural Banks in Bali. To answer the hypothesis proposed in this study, the data were analyzed using path analysis with AMOS program 16. The results showed that Capital Adequacy Ratio has a positive influence on Return On Assets. Operational Revenue Operating Expense (BOPO) has a negative effect on Return On Assets. Loan to Deposit Ratio (LDR) has a positive effect on Return On Assets (ROA). Net Interest Margin (NIM) has a positive influence on Return On Assets (ROA). Capital Adequacy Ratio (CAR) has a positive effect on Profit Change. Operating Revenue Operating Expenses (BOPO) have a negative effect on Profit Change. Loan to Deposit Ratio has a positive effect on Profit Change. Net Interest Margin has a positive influence on Profit Change. Return On Assets (ROA) has a positive effect on Profit Change.